Effects of Total Abdominal Hysterectomy and Total Laparoscopic Hysterectomy on Urinary Tract Dysfunction - Gökmen Sukgen; Ünal Türkay (Wolters Kluwer Medknow Publications, 2020)
Objectives: The aim of this study is to compare the urinary tract dysfunction rates of total abdominal hysterectomy (TAH) and total laparoscopic hysterectomy. Materials and Methods: Turkish patients who underwent TAH and laparoscopic hysterectomy were invited to participate in this study. In this study, 140 patients were examined who underwent hysterectomy in gynecology clinic between 2013 and 2018. The post residual urine volumes of patients were measured in the preoperative period and 8th week of the postoperative period as urodynamic evaluation (with office cystometry and Q tip test). Statistical analysis was performed using Kruskal-Wallis Mann-Whitney U test by using SPSS 22.0 statistical program. Results: No statistical significance (P > 0.05) was found between age, parity, menopause, and obesity in our patients who underwent TAH and laparoscopic hysterectomy with high postvoid residual values in the postoperative period. Conclusion: In this study, no statistical significance was found between the hysterectomy techniques on urinary tract dysfunction. It can be said that laparoscopy should be more preferable in correctly selected patients for minimal dysfunctional complications.